Effects of Andrographis paniculata Leaf Extract on Immune Response and Disease Resistance in Tilapia against Aeromonas hydrophila Infection - RAJENDRAN, VIJAYAKUMAR; Faiz Al Faiz (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2025)
The prolonged use of antibiotics in aquaculture has increase a chances of getting antimicrobial resistance and need necessitating effective alternatives. Medicinal plants, such as Andrographis paniculata, give a promising solution due to their antimicrobial and immunostimulatory properties. This study investigated the effects of dietary supplementation with A. paniculata leaf extract on the immune response and disease resistance of Mozambique tilapia, Oreochromis mossambicus. Fish were fed diets containing varying concentrations of aqueous and ethanolic leaf extracts for 30 days. A comprehensive analysis of non-specific immune parameters was subsequently conducted on serum samples. The extract demonstrated significant in vitro antibacterial and anti-biofilm activity against A. hydrophila. Dietary administration of A. paniculata significantly improved key cellular immune responses, which includes serum myeloperoxidase activity, respiratory burst activity, and nitric oxide production. Humoral immunity was also fortified, as evidenced by increased activities observed in serum anti-protease, natural haemolytic complement, lysozyme, and alkaline phosphatase. Furthermore, a marked increase in the antioxidant enzyme catalase and total serum protein was observed in treated groups. The immunostimulatory effects translated into superior disease resistance. Following a challenge with a lethal dose of A. hydrophila, fish fed the A. paniculata-supplemented diets demonstrated a significantly greater survival rate compared to the control group. The results conclusively demonstrate that A. paniculata leaf extract is a potent dietary immunostimulant that enhances both humoral and cellular immune mechanisms in O. mossambicus. Its application significantly improves survival against aeromoniasis, presenting a viable, natural strategy for sustainable health management in aquaculture.